Zarządzanie organizacjami pozarządowymi: Management of non-governmental organizations - Huczek, Marian (Management and Administration Journal, 2021)
The article presents the conditions of development and functioning of nongovernmental organizations and on this background it shows the problems of management of those organizations. It characterizes the respective groups of stakeholders of nongovernmental organizations and indicates the necessity to analyze the power of influence of the stakeholders on a given organization and management of the relationships formed between them and the non-governmental organizations. Furthermore, the article defines the goals, mission and the essence of strategic management in the organizations.